some noun paradigms - Dagny Hildegard Skaile; Joshua Karl Wilbur (Joshua Wilbur, 2011)
Linguistic documentation of the Pite Saami language (ISO693-3: sje) noun paradigms for eddno (maternal uncle), edno (river), båtsoj (reindeer); båtsoj includes elicitation of it with numerals and quantifiers